Kinerja Aparatur Pemerintah Dalam Pelayanan e-KTP di Kantor Camat Cisarua Kabupaten Bandung Barat - Pipip Susilawati; Arland Sidra; Dadang Sufianto (MIMBAR ADMINISTRASI FISIP UNTAG Semarang, 2024)
This study analyzes the performance of e-KTP services at the Cisarua Sub-district Office, West Bandung Regency, focusing on four main indicators: quality, quantity, task implementation, and responsibility. The method used is in-depth interviews with seven informants, involving officers and the community involved in the e-KTP service process. The findings revealed significant challenges such as inadequate infrastructure, technical problems, lack of human resources, inefficient procedures, and disciplinary problems. The conclusion of this study is that improving the performance of e-KTP services can be achieved through intensive and continuous training for human resources, updating information technology systems, and simplifying service procedures. The implementation of these solutions is expected to accelerate the service process, reduce waiting times, and increase public satisfaction with e-KTP services at the Cisarua Sub-district Office.